New Miscanthus hybrids cultivated at a Polish metal-contaminated site demonstrate high stomatal regulation and reduced shoot Pb and Cd concentrations. (September 2019) - Rusinowski, Szymon; Krzyżak, Jacek; Clifton-Brown, John; Jensen, Elaine; Mos, Michal; Webster, Richard; Sitko, Krzysztof; Pogrzeba, Marta
Abstract: The increased bioeconomy targets for the biomass share of renewable energy production across Europe should be met using land unsuitable for food production. Miscanthus breeding programs targeted the production of plants with a diverse range of traits allowing a wider utilization of land resources for biofuel production without competing with arable crops. These traits include increasing tolerances to drought, chilling, and to metal(loid)s excess. Two novel Miscanthus hybrids, GNT41 and GNT34, were compared against Miscanthus x giganteus ( M x g ) on metal-contaminated arable land in Poland. This study aimed at evaluating their yield, biomass quality and quantifying seasonal differences in photosynthetic and transpiration parameters. A secondary objective was to identify key physiological mechanisms underlying differences in metal accumulation between the investigated plants. The new hybrids produced a similar yield to M x g (13–15 t ha −1 yr −1 ), had shorter shoots, higher Leaf Area Index and stem number. Based on gas exchange measurements, GNT34 exhibited isohydric (water-conserving) behavior. The stomatal response to light of the new hybrids was at least twice as fast as that of M x g, a trait that is often associated with increased seasonal water use efficiency. This contributed to the almost 40% reduction in shoot Pb and Cd concentrations for the new hybrids as compared to M x g . This suggested that promoting stomatal regulation in conjunction with improved water conservation may be a target for improving plants for wider use on metals contaminated land. Graphical abstract: High yielding Miscanthus hybrids with combined drought resilience and fast stomatal response produced less contaminated biomass.Image 1 Highlights: Miscanthus spp. plantation was established on metal-contaminated arable land. All investigated plants produce similar yield, ca. 13–15 t ha −1 yr −1 . New, seed-based hybrids, showed more water-conserving behavior than M. x giganteus . Plants exhibiting more isohydric behavior had lower shoot Pb and Cd concentrations.